Methylated H3K4, a transcription-associated histone modification, is involved in the DNA damage response pathway. - David Faucher; Raymund J Wellinger (PLoS Genetics)
Eukaryotic genomes are associated with a number of proteins such as histones that constitute chromatin. Post-translational histone modifications are associated with regulatory aspects executed by chromatin and all transactions on genomic DNA are dependent on them. Thus, it will be relevant to understand how histone modifications affect genome functions. Here we show that the mono ubiquitylation of histone H2B and the tri-methylation of histone H3 on lysine 4 (H3K4me3), both known for their involvement in transcription, are also important for a proper response of budding yeast cells to DNA damaging agents and the passage through S-phase. Cells that cannot methylate H3K4 display a defect in double-strand break (DSB) repair by non-homologous end joining. Furthermore, if such cells incur DNA damage or encounter a stress during replication, they very rapidly lose viability, underscoring the functional importance of the modification. Remarkably, the Set1p methyltransferase as well as the H3K4me3 mark become detectable on a newly created DSB. This recruitment of Set1p to the DSB is dependent on the presence of the RSC complex, arguing for a contribution in the ensuing DNA damage repair process. Taken together, our results demonstrate that Set1p and its substrate H3K4me3, which has been reported to be important for the transcription of active genes, also plays an important role in genome stability of yeast cells. Given the high degree of conservation for the methyltransferase and the histone mark in a broad variety of organisms, these results could have similar implications for genome stability mechanisms in vertebrate and mammalian cells.